The role of GLP-1 analogues, including oral semaglutide, in the treatment of type 2 diabetes – based on clinical trial results and current guidelines - Gręblowski, Piotr; Łosiowska, Anna; Kłoda, Karolina (Lekarz POZ, 2024)
Guidelines of scientific societies indicate a key role of GLP-1 (glucagon-like peptide-1) analogues in the treatment of type 2 diabetes mellitus, especially in patients who are overweight, living with obesity, and are at increased cardiovascular risk. Although this group primarily includes drugs in the form of subcutaneous injection, there is also an oral formulation available. Oral semaglutide is an effective, non-invasive method of treating type 2 diabetes mellitus. This has been proven in numerous studies, in which the effectiveness of oral semaglutide in reducing glycated haemoglobin value in adult patients with type 2 diabetes mellitus, in whom previous therapy did not provide adequate control of the disease, was assessed. It has also been shown to be effective in terms of weight loss. Semaglutide can also be safely used in patients with renal failure, in whom it additionally shows a nephroprotective effect.